2017
DOI: 10.15376/biores.12.4.8240-8254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study on pyrolysis characteristics and kinetics of corn stover and its digestate by TG-FTIR

Abstract: The pyrolysis potential of corn stover digestate (CSD) was compared with corn stover (CS). The effects of anaerobic digestion (AD) on pyrolysis were investigated at different rates by a thermogravimetric analyzer coupled with Fourier transform infrared spectrometry (TG-FTIR). The distributed activation energy model (DAEM) was used to show the differences in the kinetics. The results indicated that the AD process improved the thermal stability with lower mean reactivity (RM), higher solid residue (S850), and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…No data for E α of digestates composed of SS and lignocellulosic biomass can be found in the literature. Nevertheless, some correlations could be made with swine manure digestate [45], corn stover digestate [88], roadside grass digestate [85], and other lignocellulosic rich digestates [25,44]. As shown in Table 4, the E α varied greatly with the type of feedstock.…”
Section: Activation Energy ( )mentioning
confidence: 99%
“…No data for E α of digestates composed of SS and lignocellulosic biomass can be found in the literature. Nevertheless, some correlations could be made with swine manure digestate [45], corn stover digestate [88], roadside grass digestate [85], and other lignocellulosic rich digestates [25,44]. As shown in Table 4, the E α varied greatly with the type of feedstock.…”
Section: Activation Energy ( )mentioning
confidence: 99%
“…The studied components are the carbon dioxide, carbon monoxide, H 2 O, methane, aldehydes and ketones, alcohols and esters. The mentioned compounds can be identified as C=O (2400-2250 cm −1 ), C-O (2250-2000 cm −1 ), O-H (4000-3400 cm −1 ), C-H (3000-2842 cm −1 ), C=O (1800-1684 cm −1 ) and C-O-H (1131-1058 cm −1 ) functional groups [28]. Observing the FTIR spectra, it was noted that the individual peak temperatures appeared around 350-380 • C; moreover, the main degradation occurred between 200 and 600 • C, resulting in a great number of organic volatiles in the devolatilization/pyrolysis zone.…”
Section: Ftir Analysismentioning
confidence: 99%
“…However, a major limitation of the DAEM is that it is difficult to estimate kinetic parameters due to complexity of the model. Also, it assumes that reaction proceeds through infinite and irreversible number of independent parallel reactions [55,56]. Kumar et al [57] reported that the Starink model uses approximation and empirical relation between reaction rate and temperature, hence other iso-conversional models such as Flynn-Wall-Ozawa (FWO) are considered to be better [57].The thermal pyrolysis/combustion of SD is considered an endothermic [39] and non-adiabatic process, as a result heat released can lead to a rapid rise in temperature alongside gas release [2].…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been very few kinetic modelling studies for the pyrolysis of digestate [55,58], although these have only reported limited details of the feedstocks for the AD process.…”
Section: Introductionmentioning
confidence: 99%